PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI, DAN ARUS KAS PENDANAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2019 - Baru Harahap; Syahril Effendi (JURNAL AKUNTANSI BARELANG, 2020)
This study aims to determine the effect of cash flows from operating, investing, and financing to saham Return. Data obtained from the income statement, cash flow statement, as well as saham market prices daily on Textile companies listed on the Saham Exchange 2014-2019. The analytical tool used is multiple linear regression, F test and t test. The samples are 15 companies Textile sector during the period 2014-2019. Based on the survey results revealed that a significant difference between cash flows from operating, investing, and financing on saham Returns with sig <0.05. T test results of each independent variable cash flows from operating, investing, and financing an effect on saham Returns (Returns) with sig < 0.05. The conclusion that can be drawn is that the investors who want to invest their shares in the company on the Indonesian Saham Exchange should pay attention to the ratio of a company's cash investment object, because of the results showed that the cash flow effect on saham Returns